Expanding the repertoire of conservative site-specific recombination in Clostridioides difficile. (December 2019) - Sekulovic, Ognjen; Bourgeois, Jacob; Shen, Aimee; Camilli, Andrew
Abstract: Recent genomic analysis of an epidemic ribotype 027 (RT027) Clostridioides difficile strain revealed the presence of several chromosomal site-specific invertible sites hypothesized to control the expression of adjacent genes in a bimodal on-off mode. This process, named phase variation, is thought to enhance phenotypic variability under homogeneous conditions ultimately increasing population fitness in unpredictable environmental fluctuations. The full extent of phase variation mediated by DNA-inversions in C. difficile is currently unknown. Here, we sought to expand our previous analysis by screening for site-specific inversions in isolates that belong to the rapidly emerging ribotypes RT017 and RT078. We report the finding of one novel inversion site for which we demonstrate the inversion potential and quantify inversion proportions during exponential and stationary growth in both historic and modern isolates of the same ribotype. We then employ a computational approach to assess the prevalence of all sites identified so far in a large collection of sequenced C. difficile isolates. We show that phase-variable loci are widespread with some sites being present in virtually all analyzed strains. Furthermore, in our small subset of RT017 and RT078 strains, we detect no evidence of gain or loss of invertible sites in historic versus modern isolates demonstrating the relative stability of those genomic elements. Overall, our results support the idea that C. difficile has adopted phase variation mediated by DNA inversions as its major generator of diversity which could be beneficial during the pathogenesis process. Highlights: C. difficile ribotype 017 complex encodes a novel conservative site-specific inversion site. Inversion sites show widespread prevalence within C. difficile species. We detected shuffling patterns in prophage regions in C. difficile genomes.